In an open publishing house not so far, far away…. Issue 4 (July 2016) - Kaufman, Kenneth R.; Malhi, Gin S.; Baxter, Amanda; Bhui, Kamaldeep
Summary: As BJPsych Open completes its first circle around the sun and marks its first anniversary, we share with you its strengths and advantages that underpin its success as a new journal. First and foremost, the editorial team has maintained rigorous scientific standards while pursuing an open access publishing model that, by design, accommodates a broad range of clinical and scientific topics. Fundamental to BJPsych Open 's mission has been our policy of accepting papers that are both methodologically sound and intellectually stimulating. The calibre of the journal has already been recognised, with recent notification of indexing all its content in PubMed Central. This reflects the quality of submissions and is the result of concerted efforts by the authors, the editorial board, the many selfless reviewers and our dedicated staff in the journal office. We urge you to join us on this exciting journey and look to your input as authors, readers and reviewers to help shape this fledgling enterprise, destined to become a force to be reckoned with.